Genome-Wide Identification of FCS-Like Zinc Finger (FLZ) Family Genes in Three Brassica Plant Species and Functional Characterization of BolFLZs in Chinese Kale Under Abiotic Stresses - Zhao, Yuwan; Chen, Shunquan; Qin, Mao; Shui, Kejuan; Li, Riqing; Yang, Baoli; Liu, Jin; Chen, Zhufeng (International journal of molecular sciences, 2024)
FCS-like zinc finger (FLZ) proteins are plant-specific regulatory proteins, which contain a highly conserved FLZ domain, and they play critical roles in plant growth and stress responses. Although the FLZ family has been systematically characterized in certain plants, it remains underexplored in Brassica species, which are vital sources of vegetables, edible oils, and condiments for human consumption and are highly sensitive to various abiotic stresses. Following the whole-genome triplication events (WGT) in Brassica, elucidating how the FLZ genes have expanded, differentiated, and responded to abiotic stresses is valuable for uncovering the genetic basis and functionality of these genes. In this study, we identified a total of 113 FLZ genes from three diploid Brassica species and classified them into four groups on the basis of their amino acid sequences. Additionally, we identified 109 collinear gene pairs across these Brassica species, which are dispersed among different chromosomes, suggesting that whole-genome duplication (WGD) has significantly contributed to the expansion of the FLZ family. Subcellular localization revealed that six representative BolFLZ proteins are located in the nucleus and cytoplasm. Yeast two-hybrid assays revealed that 13 selected BolFLZs interact with BolSnRK1α1 and BolSnRK1α2, confirming the conservation of the SnRK1α-FLZ module in Brassica species. Expression profile analysis revealed differential expression patterns of BolFLZ across various tissues. Notably, the expression levels of seven BolFLZ genes out of the fifteen genes analyzed changed significantly following treatment with various abiotic stressors, indicating that the BolFLZ genes play distinct physiological roles and respond uniquely to abiotic stresses in Brassica species. Together, our results provide a comprehensive overview of the FLZ gene family in Brassica species and insights into their potential applications for enhancing stress tolerance and growth in Chinese kale.